An Efficient and Environmentally Benign Diversity-Oriented Multicomponent Synthesis of Privileged Substructures Based Spirooxindoles Using TiO2 Nanoparticles as Heterogeneous Catalyst - Kulhari, Anju; Khandelwal, Sarita; Gupta, Kalpana; Jain, Hemant Kumar; Gopal, Ram; Kumar, Mahendra (Current Catalysis, 2016)
Background: The development of novel synthetic methods for the preparation of structurally diverse drug-like molecules expeditiously and efficiently utilizing simple and readily available starting materials and easy experimental procedure with environmentally friendly solvent and catalyst is significant not only in the advancement of chemical research but also in the development of drug discovery research. Multicomponent reactions (MCR) are considered to be powerful and efficient synthetic methodology for building highly diverse complex organic molecules of biological relevance with high atom-economy, high selectivity, high purity and excellent yields. In the present research work, the synthetic potentialities of multicomponent reactions have been combined with the green chemistry to develop diversity oriented synthesis of structurally diverse spirooxindoles spiroannulated with benzo[a]xanthene, benzo[f]indanochromene, benzo[f]pyranochromene and benzo[f]chromenochromene with drug-like complexity and promising bioactivity. Method: Spirooxindoles spiroannulated with benzo[a]xanthene, benzo[f]indanochromene, benzo[f]pyranochromene and benzo[f]chromenochromene have been synthesized by the present synthetic protocol involving multicomponent reaction of substituted isatins, β-naphthol and 1,3-dicarbonyl compounds in aqueous ethanol [C2H5OH:H2O (v:v/1:5)] using TiO2 nanoparticles as recyclable and reusable environmentally benign catalyst. Results: We have presented an efficient and eco-compatible diversity oriented synthetic protocol for the synthesis of spirooxindoles spiroannulated with medicinally privileged heterocyclic substructures; benzo[a]xanthene, benzo[f]indanochromene, benzo[f]pyranochromene and benzo[f]chromenochromene in good to excellent yields using TiO2 nanoparticles as recyclable and reusable heterogeneous catalyst. TiO2 nanoparticles facilitate the reaction and play an important catalytic role with the involvement in the reaction mechanism. Conclusion: The potentialities of the waste-free synthetic protocol combined with recyclability and reusability of the catalyst make this method economic and environmentally benign for the synthesis of spiroheterocycles incorporating three-four medicinally privileged heterocyclic substructures. In addition, excellent yields, short reaction times, mild reaction conditions, avoiding hazardous organic solvents, and experimental simplicity with easy work-up are some interesting features of the present synthetic protocol which indicate novelty and synthetic utility of the present protocol to synthesize drug-like molecules with structural diversity and molecular complexity.
Keywords: benzo[f]chromenochromene